2011
DOI: 10.1002/hon.1014
|View full text |Cite
|
Sign up to set email alerts
|

Role of platelet‐derived growth factor‐AB in tumour growth and angiogenesis in relation with other angiogenic cytokines in multiple myeloma

Abstract: Angiogenesis is a complex process essential for the growth, invasion, and metastasis of various malignant tumours, including multiple myeloma (MM). Various angiogenic cytokines have been implicated in the angiogenic process. Among them, platelet-derived growth factor-AB (PDGF-AB) has been reported to be a potent stimulator of angiogenesis in many solid tumours and haematological malignancies, including MM. The aim of the study was to investigate the relationship between PDGF-AB, microvascular density (MVD), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 34 publications
1
21
0
Order By: Relevance
“…This indicates that MM patients who present with a high angiogenic status, translated to a high MVD count, run a 85% greater risk of death than MM patients with low angiogenic status at diagnosis. Several individual studies have demonstrated poor survival for MM patients with high MVD status [36,37,51,52,53,56,57,58,59,60,61,62,63]; our study based on a validated statistical methodology further strengthens this conclusion. More specifically, this meta-analysis, by integrating for the first time the existing data from individual reports, proves that that MVD can be considered as a surrogate marker of survival for MM patients as well as provide a novel, pooled estimation of the impact of angiogenesis in this disease.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…This indicates that MM patients who present with a high angiogenic status, translated to a high MVD count, run a 85% greater risk of death than MM patients with low angiogenic status at diagnosis. Several individual studies have demonstrated poor survival for MM patients with high MVD status [36,37,51,52,53,56,57,58,59,60,61,62,63]; our study based on a validated statistical methodology further strengthens this conclusion. More specifically, this meta-analysis, by integrating for the first time the existing data from individual reports, proves that that MVD can be considered as a surrogate marker of survival for MM patients as well as provide a novel, pooled estimation of the impact of angiogenesis in this disease.…”
Section: Discussionsupporting
confidence: 73%
“…Furthermore, many previous studies have demonstrated the clinical significance of angiogenesis in MM, and the majority of them have correlated the high MVD count with poor prognosis [36,37,51,52,53,54,55,56,57,58,59,60,61,62,63]. …”
Section: Introductionmentioning
confidence: 99%
“…We investigated whether PDGFRA and PDGFRB has significant co-occurrence with ITGA8 using the cBioPortal genome database, and the results were consistent with our finding that increasing integrin-α8 expression induced PDGFRA and PDGFRB mRNA expression. PDGFR signaling has been thoroughly investigated in cancer, including MM supporting tumor growth and angiogenesis, and clinically used as a therapeutic target (Tsirakis et al, 2012; Yu et al, 2003). The PDGFR inhibitor, sunitinib, is currently in a phase II trial to test its effects on MM relapse; specifically, to determine if it can inhibit growth of cancer cells by blocking enzymes related to cancer cell proliferation and blood flow to cancer (https://clinicaltrials.gov).…”
Section: Discussionmentioning
confidence: 99%
“…17, 22 It should be emphasized that this is the first study estimating correlations between sCD40L and adhesion molecule (sVCAM-1) and growth factor (PDGF-AB) in patients with MM. It is well known that tumor growth depends on angiogenesis and lymphangiogenesis.…”
mentioning
confidence: 93%